2016
DOI: 10.1007/s12088-016-0592-6
|View full text |Cite
|
Sign up to set email alerts
|

Role of Indole Production on Virulence of Vibrio cholerae Using Galleria mellonella Larvae Model

Abstract: Cell to cell communication facilitated by chemical signals plays crucial roles in regulating various cellular functions in bacteria. Indole, one such signaling molecule has been demonstrated to control various bacterial phenotypes such as biofilm formation and virulence in diverse bacteria including Vibrio cholerae. The present study explores some key factors involved in indole production and the subsequent pathogenesis of V. cholerae. Indole production was higher at 37°C than at 30°C, although the growth at 3… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

2
16
0
1

Year Published

2018
2018
2022
2022

Publication Types

Select...
7
1
1

Relationship

0
9

Authors

Journals

citations
Cited by 16 publications
(19 citation statements)
references
References 43 publications
2
16
0
1
Order By: Relevance
“…It is important to emphasize that this work showed for the first time a very good correlation between the virulence of V. parahaemolyticus strains measured in mice and G. mellonella, indicating that this insect larva can be successfully used as an alternative and inexpensive model to study the pathogenicity of Vibrio species, as reported (Nuidate et al, 2016;Bokhari et al, 2017;Wagley et al, 2018).…”
Section: Discussionsupporting
confidence: 55%
“…It is important to emphasize that this work showed for the first time a very good correlation between the virulence of V. parahaemolyticus strains measured in mice and G. mellonella, indicating that this insect larva can be successfully used as an alternative and inexpensive model to study the pathogenicity of Vibrio species, as reported (Nuidate et al, 2016;Bokhari et al, 2017;Wagley et al, 2018).…”
Section: Discussionsupporting
confidence: 55%
“…Further, in order to determine if the inhibition of virulence assessed in vitro could also affect in vivo infection, we tested the ability of SFN to inhibit virulence of V. cholerae in a surrogate host of Galleria mellonella larvae. This model organism was described as a suitable alternative for vertebrates in selecting new antimicrobials as well as for V. cholerae infections approaches [ 57 , 58 ]. We first established the bacterial load appropriate for survival experiments ( Figure S2 ).…”
Section: Resultsmentioning
confidence: 99%
“…This assay was performed as previously described 41 , 42 using a micro-injection technique whereby 10 µl V. cholerae was injected into the haemocoel via the right foreleg, using a Hamilton syringe. G. mellonella larvae were bred in sterile conditions at 37 °C.…”
Section: Methodsmentioning
confidence: 99%